Self-organization of Small Pluripotent Stem Cells (SPSC) into EB-like Structures Under Autologous Plasma Conditions - DC, Torbjörn Ogéus; PgD,; MSc,; ScA, (Archives of Clinical and Biomedical Research, 2026)
Introduction: Rare primitive stem cell–like populations have been proposed to persist in adult tissues, including peripheral blood; however, their biological properties remain incompletely understood. In the present study, we investigated whether small peripheral blood–derived pluripotent-like cells, termed small pluripotent stem cells (SPSCs), possess an intrinsic capacity for spontaneous three-dimensional self-organization under minimal physiologic culture conditions. Methods: Peripheral blood–derived cells enriched using the Ogéus Sparq cells® platform were cultured under non-adherent conditions in either autologous plasma or isotonic saline without the addition of conventional pluripotent stem cell media or exogenous growth factors. Aggregate formation was monitored using brightfield microscopy over 72 h, while nuclear organization was evaluated using Hoechst staining. Immunofluorescence analysis was performed to assess the expression of pluripotency-associated markers SSEA-4 and SOX2. Results: SPSCs reproducibly formed compact embryoid body (EB)–like aggregates when maintained in autologous plasma, with early clustering observed within 12 h and well-defined spheroidal structures appearing by 24–48 h. By 72 h, aggregates typically measured approximately 150–220 μm in diameter. Hoechst staining revealed dense and relatively homogeneous nuclear organization throughout the aggregates, supporting the presence of a compact cellular architecture rather than hollow or necrotic cores. Immunofluorescence demonstrated SSEA-4–associated membrane staining and nuclear SOX2 expression within EB-like structures. In contrast, cells maintained in isotonic saline remained largely dispersed and failed to form comparable aggregates. Conclusions: These findings provide morphological and molecular evidence that small peripheral blood–derived cells can undergo spontaneous EB-like self-organization under physiologic plasma conditions without exogenous growth factor supplementation. Further studies will be required to determine whether these aggregates possess functional pluripotency through tri-lineage differentiation.